TEACHERS’ STRATEGIES IN TEACHING SPEAKING IN ONLINE CLASSROOM TO TOURISM VOCATIONAL SCHOOL STUDENTS - Rai Antara, I Made Agung; Anggreni, Ni Putu Yunik (Jurnal Manajemen Pelayanan Hotel, 2021)
Teaching online during the covid-19 pandemic is challenging to teachers. The challenge is to provide an interesting online learning environment to students which is the same with what they give in offline classroom. This becomes challenge because teaching online is new experience for most of the teachers. Effective teaching strategies are needed by students to prevent boredom and improve engagement in the online classroom. This study aims to describe the teachers’ strategies in teaching English online to elementary level students of Triatma Jaya vocational high school. The data was collected through interview and observation. 14 Teachers were interviewed to collect data. Data were analyzed using qualitative descriptive techniques. The result showed that teacher applied some strategies to teach online speaking, for instance interview, role play, discussion, games, and pictures. Teacher used pictures in various activities such as storytelling, describing pictures and picture narrating. However, there were some obstacles encountered while implementing these strategies, namely the unstable internet connection, insufficient knowledge of technology, students could imitate their friends work, and the amount of time spent to practice speaking in online classroom which result to students’ boredom. Keywords: strategy, speaking, online classroom.